Persepsi Pengunjung Terhadap Malini Agropark Uluwatu sebagai Daya Tarik Wisata Berbasis Pertanian di Desa Pecatu, Kecamatan Kuta Selatan, Kabupaten Badung - ANGIN, DWI SHETTY BR PERANGIN; ANGGRENI, I GUSTI AYU AGUNG LIES (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2023)
Visitors' Perception of Malini Agropark as an Agriculture-Based Tourist Attraction in Pecatu Village, South Kuta District, Badung Regency Malini Agropark is one of the agricultural-based tourist attractions in the Pecatu area. The development of the Pecatu area has become the tourism sector to date. This study aims to analyze the characteristics and perceptions of visitors to tourist attractions, namely Attraction, Amenities, Accessibility, and Ancillary. This study uses accidental sampling technique with data collection tools in the form of questionnaires and interview guidelines. The sample in the study amounted to 50 people. This study uses a quantitative qualitative descriptive analysis technique. The results of this study indicate that visitors who visit Malini Agropark Uluwatu have various types of characteristics. In the analysis results, the highest perception is the perception of facilities with a percentage of 87.92%, followed by an attraction indicator with a percentage of 87.6%, an additional service percentage of 84% and the last percentage of accessibility being 83.9%. The perception of visitors as a whole is obtained with a percentage of 84%, so the perception of visitors to tourist attractions is categorized as very good. Advise promotion to private companies, enhance the development of accessibility indicators and development Sunday Market.